If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2tan(3x) = 7 Remove parenthesis around (3x) 2ant * 3x = 7 Reorder the terms for easier multiplication: 2 * 3ant * x = 7 Multiply 2 * 3 6ant * x = 7 Multiply ant * x 6antx = 7 Solving 6antx = 7 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '6ntx'. a = 1.166666667n-1t-1x-1 Simplifying a = 1.166666667n-1t-1x-1
| 8x^2=-4x-6 | | 6(3k-2)=3(5k+1) | | -3(4n+1)=18 | | 24x^2+53x+28=0 | | b^2=15 | | g(t)=1-2 | | (2x+15)+(3x-5)=90 | | n+1-3n=-6-n-1+n | | 5n^2-17=-22 | | 60x+6y=66 | | 3(m+1)=m+9 | | 5n^2-17=22 | | -3-x+3x=5 | | b^2-8b=10 | | (2x+15)=(3x-5) | | 2tan(3x)=7 | | F(x)=4x^2-16 | | 2(x-2)=52-5x | | 103=x^2+5 | | 3(2x-3)+3(x-2)+2(2x+1)=5(x-1) | | 4x+18=35+5x | | (4x+1)=(6x-5) | | 2r^2=6r+20 | | 4x^5-20x^4-36x^3= | | 120-12(3-4(2*3-2*(-8)))= | | 5y/8-2=7y/12 | | 5(6y-5)=11(3y-2) | | F=5e-3 | | 0,36x-2,3=0,5(0,4x+1,2) | | 3x+17x-4=5(4x+2) | | g^2-28g+196= | | 3k^2=16 |